A devil and her love song. Volume 2 - Tōmori, Miyoshi (Viz Media, 2012)
"Maria's bold attitude may be exactly what she needs when she inspires an unlikely ally to come to her defense. And when she's given the task to lead her class in a choral competition, she's going to need all the gumption she can muster!" -- from publisher's web site.